Implementation of Animated Film Media in Improving the Quality of Arabic Conversation for Students of Pondok Modern Tazakka - Fatkhul Helmy; Zailani Zailani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The title ofthis research is "Implementation of Animated Film Media in Improving the Quality of Arabic Conversation of Students in Tazakka Modern Lodge" located in Batang district, Central Java.This study aims to describe the role of animated film media in improving the quality of language of Pondok Modern Tazakka students. And the method used in obtaining data in this study used qualitative methods by observing and interviewing ustadz and students of the Pondok language section. The results of observations and interviews show that animated film media is quite helpful in improving students' Arabic language skills, especially in the daily muhadatsah method of the students, where animated film media is one of the media as a support in examples of good and correct Arabic pronunciation and conversation practices. This research is qualitative type that focuses on observation and interviews descriptively and also uses several references from articles and journals.